A Very Young Adult Female Patient with Hepatitis B Flare: A Case Report - Andreas Agung Kurniawan; Ummi Maimunah (Acta Medica Indonesiana, 2023)
Hepatitis B virus (HBV) infection is a major global health problem. It can cause chronic infection and put people at high risk of death from cirrhosis and liver cancer. This study aims to present a case of chronic hepatitis B flare in a very young adult patient. An 18-year-old previously healthy female presented with jaundice developing in one week, following the previous complaints of nausea, vomiting, abdominal pain, loss of appetite, and tiredness for about three months. The patient had no risk factors for getting HBV infection, but her HBsAg-positive mother was probably an inactive HBV carrier. The hepatitis B serological testing revealed HBsAg positivity, anti-HBs seronegativity, HBeAg positivity, anti-HBe seronegativity, anti-HBc IgM seronegativity, and high levels of HBV DNA detected > 1.70 × 108 IU/mL. There was a sharp increase in serum ALT to ≥ 5-fold ULN. The abdominal ultrasonography revealed a hepatitis feature, unremarkable portal venous flow, and an extrahepatic biliary system. The liver transient elastography revealed 15.6 kPa of liver stiffness, which was in accordance with the F3-F4 fibrosis stage. These features were typical of a hepatitis B flare, the HBeAg-positive chronic hepatitis B, previously known as the immune reactive phase. A long-term nucleos(t)ide analog therapy was programmed with Tenofovir alafenamide 25 mg daily.